FAKTOR-FAKTOR PENYEBAB PENGANGGURAN DI DESA TERATAK KECMATAN RUMBIO JAYA KABUPATEN KAMPAR - Irpan Fito; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research at do at hovel village, rumbio's district dignity, Camphor regency with object is workless society at hovel village, Reason other one is there is one circumscribed skill, one that most of jobless new graduate from Senior High School that have circumscribed skill, so a lot of of their workless one.to the effect this research are subject to be know happening unemployment factor silvan hovels and any kind happening unemployment type silvan that hovel . Hovels silvan population be reach 2438 souls, and researcher takes unemployment sample 10 person, with method observationaling to utilize interview face to face or bertatapn mukan even with respondent, and with menganjukan some question.Keywords : Labour, Unemployment, Social Status